Rheological behaviour of Magnetorheological polishing fluid for Si polishing. (2017) - Saraswathamma, K.; Jha, Sunil; Venkateswara Rao, P.
Abstract: The finishing mechanism of the magnetorheological finishing (MRF) process primarily depends on the Magnetorheological polishing (MRP) fluid, which acts as a tool in finishing the component surfaces. MRP fluid imparts strength to the polishing spot under the applied magnetizing currents/magnetic field strength. Behaviour of this fluid mainly influenced by the size and shape of its constituents, volume concentration, particle size distribution, and applied magnetic field strength. A detailed study was undertaken on the role of carbonyl iron particle (CIP) and abrasive size on the rheological behaviour of the MRP fluid under various magnetic flux densities. Rheological characterization study was carried out using three different models such as Bingham plastic model, Herschel-Bulkley model and Casson fluid model. MRP fluid rheological properties such as yield stress and viscosity were evaluated using parallel plate magnetorheometer.